Stuttering priapism post C-spine schwannoma excision: case report - Agwu, Ngwobia Peter; Lasseini, Ali (International Surgery Journal, 2020)
Priapism is prolonged penile erection that persists beyond or is unrelated to sexual stimulation and this is associated with significant psychological, socioeconomic and physical morbidity. It is a urologic emergency as delayed intervention may result in penile fibrosis and consequent erectile dysfunction. The aim of this paper is to present our experience in the management of the rare occurrence of stuttering priapism in a 32 years old man following surgical excision of cervical schwannoma during the early postoperative period and review relevant literature on management of this urologic entity. Stuttering priapism may complicate cervical spine tumor excision but may demonstrate complete patient recovery.